Loss of Bacteroides thetaiotaomicron bile acid-altering enzymes impacts bacterial fitness and the global metabolic transcriptome - Arthur S. McMillan; Matthew H. Foley; Caroline E. Perkins; Casey M. Theriot (Microbiology Spectrum, 2024)
ABSTRACT Bacteroides thetaiotaomicron (B. theta) is a Gram-negative gut bacterium that encodes enzymes that alter the bile acid pool in the gut. Primary bile acids are synthesized by the host liver and are modified by gut bacteria. B. theta encodes two bile salt hydrolases, as well as a hydroxysteroid dehydrogenase. We hypothesize that B. theta modifies the bile acid pool in the gut to provide a fitness advantage for itself. To investigate each gene’s role, different combinations of genes encoding bile acid-altering enzymes (bshA, bshB, and hsdhA) were knocked out by allelic exchange, including a triple KO. Bacterial growth and membrane integrity assays were done in the presence and absence of bile acids. To explore if B. theta’s response to nutrient limitation changes due to the presence of bile acid-altering enzymes, RNA sequencing (RNASeq) analysis of wild type (WT) and triple knockout (KO) strains in the presence and absence of bile acids was done. WT B. theta is more sensitive to deconjugated bile acids such as cholate, chenodeoxycholate (CDCA), and deoxycholate (DCA) compared with the triple KO. These deconjugated bile acids also decreased membrane integrity of both WT and triple KO. The presence of bshB is detrimental to growth in conjugated forms of CDCA and DCA. RNASeq analysis also showed that bile acid exposure impacts multiple metabolic pathways in B. theta, but DCA significantly increases expression of many genes in carbohydrate metabolism, specifically those in polysaccharide utilization loci or PULs, in nutrient-limited conditions. This study suggests that bile acids B. theta encounters in the gut may signal the bacterium to increase or decrease its utilization of carbohydrates. Further study looking at the interactions between bacteria, bile acids, and the host may inform rationally designed probiotics and diets to ameliorate inflammation and disease. IMPORTANCE Recent work on bile salt hydrolases (BSHs) in Gram-negative bacteria, such as Bacteroides, has primarily focused on how they can impact host physiology. However, the benefits bile acid metabolism confers to the bacterium that performs it are not well understood. In this study, we set out to define if and how Bacteroides thetaiotaomicron (B. theta) uses its BSHs and hydroxysteroid dehydrogenase to modify bile acids to provide a fitness advantage for itself in vitro and in vivo. Genes encoding bile acid-altering enzymes were able to impact how B. theta responds to nutrient limitation in the presence of bile acids, specifically carbohydrate metabolism, affecting many polysaccharide utilization loci. This suggests that B. theta may be able to shift its metabolism, specifically its ability to target different complex glycans including host mucin, when it comes into contact with specific bile acids in the gut.